Habitat effects on golden‐cheeked warbler productivity in an urban landscape - Dianne H. Robinson; Heather A. Mathewson; Michael L. Morrison; R. Neal Wilkins (Wildlife Society Bulletin)
ABSTRACT Habitat fragmentation and isolation can result in decreased occupancy and reproductive success within songbirds, particularly for species inhabiting urban environments where available habitat may be limited. The golden‐cheeked warbler (Setophaga chrysoparia) is a federally endangered songbird that inhabits oak–juniper (Quercus spp.–Juniperus spp.) woodlands across central Texas, USA. Past research has indicated decreased patch occupancy and productivity near urban areas. We monitored patch occupancy, territory establishment, pairing success, and fledging success of warblers in an urban environment. Warblers occupied 24% (n = 63) of patches surveyed; 10% (n = 63) of habitat patches had ≥1 established territory. Warblers successfully paired in 4 patches and fledged young in 3 patches. We found an increasing probability of occupancy at approximately 65–70% canopy cover, and an added effect of distance to the nearest habitat patch. We found that distance to and size of the nearest habitat patch best predicted territory establishment. Patch size and size of the nearest habitat patch best predicted pairing success. Although our results were inconclusive for fledging success, a review of available data suggests patch size, size of, and distance to the nearest habitat patch all affect warbler reproductive activity. We recommend to manage for oak–juniper woodland patches with >70% canopy cover that are >26 ha in size, in close proximity to other oak–juniper woodland patches with equal or greater canopy cover and patch size when managing for golden‐cheeked warblers within an urban matrix. © 2018 The Wildlife Society.